1990
DOI: 10.3758/bf03205980
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual interaction of graphical attributes: Configurality, stimulus homogeneity, and object integration

Abstract: Researchers have proposed that graphical efficacy may be determined, in part, by the nature of the perceptual interactions that exist between attributes used to create graphical displays, One extreme type of interaction is integrality, in which two or more physical dimensions are represented as a single psychological dimension in the observer. An alternative type of interaction is configurality, in which a global emergent dimension is available to the observer in addition to the component attributes, Thirteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…Since there is no interaction between the dimensions, performance on the condensation task suffers accordingly (Bennett and Flach, 1992). Psychological studies suggest that the following stimulus dimensions are separable: size and value (Handel and Imai, 1972;Gottwald and Garner, 1975;Garner, 1977;Kemler and Smith, 1979;Smith, 1980), size of circle and angle of diameter (Garner and Felfoldy, 1970;Schumann and Wang, 1980), the tilt of a line within a form (Egeth, 1966), color and orientation (Carswell and Wickens, 1990), and the orientation of multiple lines (Carswell and Wickens, 1990).…”
Section: Relevant Literature Selective Attention Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no interaction between the dimensions, performance on the condensation task suffers accordingly (Bennett and Flach, 1992). Psychological studies suggest that the following stimulus dimensions are separable: size and value (Handel and Imai, 1972;Gottwald and Garner, 1975;Garner, 1977;Kemler and Smith, 1979;Smith, 1980), size of circle and angle of diameter (Garner and Felfoldy, 1970;Schumann and Wang, 1980), the tilt of a line within a form (Egeth, 1966), color and orientation (Carswell and Wickens, 1990), and the orientation of multiple lines (Carswell and Wickens, 1990).…”
Section: Relevant Literature Selective Attention Theorymentioning
confidence: 99%
“…Furthermore, configural dimensions will facilitate the condensation task because the emerging property can be used as the basis for classification (Bennett and Flach, 1992). Psychological research has found that the repeated used of the same dimension promotes configurality (Garner, 1978;Carswell and Wickens, 1990). Other stimulus dimensions that have been identified as configural include vertical symmetry and parallelism (Pomerantz and Garner, 1973;Pomerantz and Pristach, 1989), as well as the vertical extents of line graphs and the orientations of folding fans (Carswell and Wickens, 1990).…”
Section: Relevant Literature Selective Attention Theorymentioning
confidence: 99%
“…Earlier studies mainly demonstrated the importance of spatial design characteristics for integration processes within different task requirements (Carswell & Wickens, 1990;Gillan, 1995;Lohse, 1991). However, in the past 12 years, influential studies have emerged that have been explicitly devoted to integration processes (e.g., Bryant & Tversky, 1999;Zacks & Tversky, 1999).…”
mentioning
confidence: 99%
“…Developing principles for designing effective diagrams has been a concern of graphic designers (e.g., Horn, 1998;Mijksenaar & Westentorp, 1999;Tufte, 1983Tufte, , 1990Tufte, , 1997, cognitive scientists (e.g., Carswell & Wickens, 1990;Kieras & Bovair, 1984;Kosslyn, 1994;Larkin & Simon, 1987;Narayanan & Hegarty, 1998;Novick, 2001;Pinker, 1990;Stenning & Oberlander, 1995;Tversky, 1995Tversky, , 2001Tversky et al, in press), statisticians (e.g., Cleveland, 1985;Wainer, 1984;Wilkinson, 1999), semioticians (Bertin, 1983;McCloud, 1994), computer scientists (e.g., Card, Mackinlay, & Shneiderman, 1999;Glasgow, Narayanan, & Chandrasekeran, 1995;Ware, 2000), classicists (e.g., Netz, 1999;Small, 2003), and educators (e.g., Mayer, 2001;Winn, 1987). Here we focus on diagrams of mechanical systems, a domain of interest in many cognitive, computer, and educational inves-tigations (e.g., Hegarty & Just, 1993;Kieras and Bovair, 1984;Mayer & Gallini, 1990).…”
Section: Introductionmentioning
confidence: 99%